Tinkering to Fabricating-Developing Basic Skills of Fabrication in Freshmen - Kavale, Sanjeev M.; Patil, Adarsh; Choukimath, Mantesh; Shivalli, Basangouda (Journal of Engineering Education Transformations, 2025)
Developing the basic skills of fabrication and its knowledge is an important part of engineering curriculum. An immediate necessity could be during student project activities. Students, sometimes irrespective of different streams of engineering, will develop a prototype or Proof of Concept of a system as their Project. This involves invariably usage of different tools at workshop like Files, Drilling Machine, Bench Vice, Hack Saw Blade, etc. Developing these basic fabrication skills has been done through various methods in different universities. One such experiment was conducted in the name of "Design Project" for freshmen at KLE Tech, Hubballi. The prime objective of this work was to check the effectiveness of learning on various basic fabrication skills through Design Project. In this work, effort has been made to introduce workshop as a tutorial component of Basic Mechanical Engineering (BME) Course Curriculum. This course is of 3 credits, out of which 2 are for class room sessions and 1 for tutorial session. Demonstration on usage of tools was given to students during tutorials. To check effectiveness of tutorial component, design project was introduced. After the completion of the course, an anonymous feedback taken by the students revealed that BME curriculum and design project were enjoyable learning processes. 50% of the students agreed that Design Project was the most wonderful project experience. 90% of the students agreed that BME curriculum was exciting. 81% of them agreed that they were able to use different workshop tools for Design Project comfortably. Based on the results of the work, it appears that Design Project along with BME curriculum with Workshop content as Tutorial component could be significantly beneficial. This article showcases the benefits of present model along with BME curriculum with tutorial component, conduct of design project, its assessment and review of feedback taken by the students.